Dinamika Pengembangan Ilmu Falak di Pesantren - Fitri Kholilah (JURNAL PENELITIAN, 2017)
Since the beginning of its development in Indonesia, astronomy (falak) cannot be separated from pesantren. After receiving lessons from their teachers, the scholars then taught this knowledge (falak) to the santri in the pesantren. Based on observation, there are several boarding schools that have developed falak knowledge, such as Pondok Pesantren Al-Hikmah 2 Brebes, Central Java; Pondok Pesantren Salafiyah Kajen Pati, Central Java; Pondok Pesantren Tremas Pacitan, East Java; Pondok Pesantren Lirboyo Kediri; and Pondok Pesantren Al-Falah Ploso Kediri, East Java. This research uses a field research approach through observation, documentation, and interviews. The results of this study indicate that the five pondok pesantren are permanent institutions and are quite serious in the development of the science of astronomy, as evidenced by incorporating the science of falak into the learning curriculum. In general, the development model of astronomy implemented by the boarding schools mentioned above is to combine the two calculation theories, namely classical and contemporary theory.